A problem for one class of pseudodifferential evolutionary equations multipoint in the time variable - Verezhak, A. P.; Horodets’kyi, V. V.; Petryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish the correct solvability of the multipoint (in the time variable) problem for the evolution equation with operator of differentiation of infinite order in generalized S-type spaces. The properties of the fundamental solution of this problem and the behavior of the solution u(t, x) as t → +∞ are investigated.